The Effect Of Financial Ratio On Firm Value: Food and Beverage Sector Listed In IDX - Yandi Suprapto; Lindawati Lindawati (Islamic University of Kalimantan MAB Banjarmasin, 2023)
A company is established with the aim of achieving profits and prosperity for company owners and shareholders in an industry. However, not all standing companies get maximum profits, so this study aims to determine whether the independent variables of financial ratios such as dividend policy, investment decision, leverage, profitability and firm size can affect the dependent variable firm value. This study took samples from companies listed on the IDX engaged in the food and beverage sector in 2017-2021 with the final sample used to conduct the research as many as 62 companies. The method of data analysis in this study uses the panel regression method which is useful for predicting and knowing the value of one variable against other variables. This research reveals that the independent variables dividend policy, investment decision and leverage have no significant effect on firm value, while the independent variables profitability and firm size have a significant but negative relationship to the dependent variable firm value.